2020
DOI: 10.1101/2020.11.19.20234120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Actionable druggable genome-wide Mendelian randomization identifies repurposing opportunities for COVID-19

Abstract: Drug repurposing provides a rapid approach to meet the urgent need for therapeutics to address COVID-19. To identify therapeutic targets relevant to COVID-19, we conducted Mendelian randomization (MR) analyses, deriving genetic instruments based on transcriptomic and proteomic data for 1,263 actionable proteins that are targeted by approved drugs or in clinical phase of drug development. Using summary statistics from the Host Genetics Initiative and the Million Veteran Program, we studied 7,554 patients hospit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 55 publications
2
47
0
Order By: Relevance
“…Increased expression of IFNAR2 reduced the risk of critical illness, consistent with IFN1 pathways in antiviral defense [16] . These findings were replicated in two further MR studies, with high IFNAR2 expression potentially conferring protection [ 34 , 41 ].…”
Section: Gwas Variants Associated With Covid-19mentioning
confidence: 66%
“…Increased expression of IFNAR2 reduced the risk of critical illness, consistent with IFN1 pathways in antiviral defense [16] . These findings were replicated in two further MR studies, with high IFNAR2 expression potentially conferring protection [ 34 , 41 ].…”
Section: Gwas Variants Associated With Covid-19mentioning
confidence: 66%
“…13,14,15 Moreover, recent studies exploring potentially important pathways for COVID-19 progression have highlighted TYK2 and its downstream signaling pathway through type 1 interferons as a potential target for treatment. 25 The existing literature can help explain the dual association between reduced risk of autoimmune conditions such as psoriasis and RA and increased risk of severe COVID via TYK2. TYK2, a member of the Janus Kinase (JAK) family of genes, plays a key role in cytokine signal transduction and the inflammatory response, particularly via IL-12, IL-23, and is also important for IL-6 and IL-10 signaling (Fig 3).…”
Section: Discussionmentioning
confidence: 99%
“…14,[27][28][29][30] However, humans with complete TYK2 LOF have clinically significant immunodeficiency with increased susceptibility to mycobacterial and viral infections. 26,31 The balance between immune tolerance and ability to mount a robust early inflammatory response, and viral host defense may in part explain the mixed results of clinical trials using immunosuppressive therapy in COVID-19 to date 25 . Corticosteroid therapy may be beneficial in later stages of COVID-19 infection but detrimental if used early in the disease presumably when an early host defense response is important.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we identified FAS as contributing specifically to severe COVID-19, but not susceptibility to infection. Gaziano et al 45 identified IFNAR2 and ACE2 as playing causal roles in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have performed Mendelian randomisation of proteins in COVID-19 44,45 . The MR analysis of Zhou et al identified OAS1 as a causal factor common to COVID-19 susceptibility, hospitalisation and very severe disease 44 .…”
Section: Discussionmentioning
confidence: 99%